PENERAPAN EVIDANCE BASE PRACTICE DENGAN METODE TERAPI MUSIK DALAM MENGATASI BURNOUT PERAWAT DIRUANG LAVENDER RSUD TARAKAN - Ratih Dimas Julianti, (2023)
Burnout is an individual's emotional response that has occurred in the long term which causes individuals to have problems with themselves including fatigue, stress and loss of motivation. The results of the BMI (Burnout Maslach Inventory) questionnaire distributed showed 17 (85%) nurses did not experience burnout 3 (15%) nurses experienced high levels of burnout. The results of distributing the questionnaires showed that three nurses needed therapy to reduce burnout. This study aims to apply Evidence Based Practice with the music therapy method in overcoming nurse burnout. The study began with the distribution of validated BMI (Burnout Maslach Inventory) questionnaires. Based on the results of the questionnaire, it was found that the problem of nurse burnout was due to increased workload. Furthermore, the researcher gave music therapy to the nurses in the middle of the nurse's shift for 30 minutes three times a week. The application of music therapy is enough to change the results of the posttest. Posttest results after the implementation of the intervention found that all nurses (100%) experienced a decrease in burnout scores to low level burnout. This phenomenon shows that the application of Evidence Based Practiced by using music therapy is proven to be able to reduce the burnout rate of nurses